Beyond lurking and posting: segmenting the members of a brand community on the basis of engagement, attitudes and identification. Issue 3 (25th September 2020) - Haverila, Matti; McLaughlin, Caitlin; Haverila, Kai C.; Arora, Mehak
Abstract : Purpose: Brand communities are an increasingly important way for brands to interact with their customers, as they give brands an opportunity to learn from and interact with people with a demonstrated interest in the brand. Literature has explored the difference between lurkers and posters within these brand communities. However, there are other ways to segment members, just as there are many ways to segment customers of products and services – and this paper aims to be a step toward going beyond simple lurking vs posting behavior as a means of differentiating community members. As such, the purpose of this paper is to segment brand communities based on not only their participation behavior but also their identification with the brand community, loyalty and benefits gained from membership. Design/methodology/approach: This study used a cross-sectional survey of members of various brand communities in North America. Partial least squares structural equation modeling together with finite mixture partial least squares and prediction-oriented segmentation was used to discover the distinct segments of brand community members. Findings: The findings indicate that there are two distinct segments that behave differently regarding their behavior, attitudes and motives. Segment one has a stronger relationship between identification and other outcomes and is also more motivated by social enhancement than segment two. Thus, it is clear that brand community members can be segmented and served based on more than their posting behavior. Originality/value: The members of brand communities have often been thought of as homogeneous. This paper is unique in identifying heterogeneity among the members of the brand community and demonstrates the need for brand community managers to identify these differences and manage the brand community accordingly.